Russian Irredentism, Authoritarian Populism, Regime Evolution, and Strategic Corruption: Current Trends in Macro Comparative Perspective - DeDominicis, Benedict Edward (The international journal of interdisciplinary global studies, 2025)
European integration functionally aims at European nation-state liberal regime stabilization. This Euro-Atlantic political high-level tactical goal does not permit minor power Bulgaria to destabilize the region through an irredentist policy toward North Macedonia. In contrast, Russia’s domestic political regime is evolving in an authoritarian populist dynamic that has intensified domestic polarization concomitantly with its escalating irredentist intervention in Ukraine. Russia is a great power. In sum, it is a state actor with a resource base that is sufficient to provide for a capability base that it needs to produce power instruments for a diplomatic bargaining base that is superior to, equal to, or very close to that of any other actor. An explication of the means by which a people submit to the authority of their state’s government serves the purpose of illustrating national morale/mobilization base in relation to resource base in capability analysis. Inferences from great power mid-twentieth century authoritarian populism are applied to the analysis of the Putin administration in Moscow. The relevance of mobilization base to power capability is also important. It is a lever toward third countries insofar as the Russian leadership perceives the European leadership as having the mobilization base to be an autonomous actor that can influence and constrain the behavior of the US. A nationalistic polity potentially has a bargaining advantage in both the short and long-term power trends, partly because of the relatively more salient and intense public predisposition to perceiving slights and dangers to the well-being and dignity of the state.